Magnetic resonance imaging of solids using oscillating field gradients - 175513 Yaacob Mat Daud (Canterbury, Eng. : University of Kent, 1992)
A fully automatic solid state NMR imaging spectrometer is described. Use has been made of oscillating field gradients to frequency and phase encode the spatial localisation of the nuclear spins. The RF pulse is applied during the zero crossing of the field gradients, so only low RF power is needed to cover the narrow spectral witd of the spins. The oscillating field gradient coils were operated on resonance lence large gradient strength could be applied (up to 200G/gm). Two image reconstruction methods were used, filtered back-projection and two dimensional Fourier transformation. The use of phase encoding, both with oscillating and with pulsed field gradients, enabled us to acquire the data when the gradients were off, and this method proved to be insensitive to eddy currents. It also allowed the use of narrow bandwidth eceiver thus improving the signal to noise ratio. The maximum entrope method was used in an effort to remove data truncation effects, although the results were too convincing. The application of these new imaging schemes, was tested by mapping the T 1 and T 2 of polymers. The calculated relaxation maps produced precise spatial information about T 1 and T 2 which is not possible to achieve by conventional relaxation weight mapping. In a second application, the diffusion of water vapour into dried zeolite powder was studied. We found that the diffusion process is not Fickian.